Transient Descending Colocolonic Intussusception Due to a Large Fecaloma in an Adult. Issue 1 (2017) - Khan, Zubair; Darr, Umar; Renno, Anas; Alkully, Turki; Rafiq, Ehsan; Sodeman, Thomas
ABSTRACT : N/A: Intussusception typically occurs in infants and children, with adults representing 5% of cases. A 53‐year‐old African American woman presented with lower abdominal pain and tenderness. Computed tomography of the abdomen and pelvis demonstrated a 3.5 cm colocolonic intussusception in the descending colon. Emergent colonoscopy found solid stool in the mid descending colon. Water‐soluble rectal enema showed a filling defect in the mid descending colon. Repeat colonoscopy demonstrated presence of a large fecaloma in left colon. Laxatives were initiated, and abdominal pain subsided. To our knowledge, this is the first report of colocolonic intussusception secondary to fecaloma.